2006
DOI: 10.1186/cc5120
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Patients in the intensive care unit (ICU) may be in an inadequate condition to give their informed consent for research. The aim of this study was to analyse the ability to recall participation in a clinical trial for which ICU patients had given their consent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…During the observations, we also found that patients ask questions about content that was already discussed by the vascular access team during the consent process. This may (1) reflect the shortcomings of the current process (ie, workload-related factors such as not spending enough time to discuss the procedure with the patient, or patient-related factors that affect comprehension such as pain and discomfort), (2) support the need for a self-paced resource such as multimedia PtDA available to patients when needed, or (3) suggest that the medical conditions of some patients in the ICUs and ACUs might be a barrier for patient engagement in the consent process [34], which advocates for the need to engage a proxy in the informed consent process [35].…”
Section: Discussionmentioning
confidence: 99%
“…During the observations, we also found that patients ask questions about content that was already discussed by the vascular access team during the consent process. This may (1) reflect the shortcomings of the current process (ie, workload-related factors such as not spending enough time to discuss the procedure with the patient, or patient-related factors that affect comprehension such as pain and discomfort), (2) support the need for a self-paced resource such as multimedia PtDA available to patients when needed, or (3) suggest that the medical conditions of some patients in the ICUs and ACUs might be a barrier for patient engagement in the consent process [34], which advocates for the need to engage a proxy in the informed consent process [35].…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about patient recall and understanding after oral versus written consent, whether that consent was granted for a research study or a clinical procedure; we therefore propose a nested study to compare these outcomes among the patients providing oral consent with those of patients providing written consent for participation in this study, as well as to outcomes of historical controls (patients providing written consent for participation in other trials, such as those followed by Chenaud et al . 35 We know that recall and understanding in the weeks after written consent are not optimal; our hypothesis is that they will not differ much (will not be significantly worse) after oral consent.…”
Section: Observational Substudiesmentioning
confidence: 94%
“…Another outcome will simply be the number of patients included in each arm, and the investigator’s cited reason for pursuing an oral versus written consent. Finally, we will perform correlation analyses for recall and understanding, looking at baseline demographic factors, other factors such as whether the patient asked a question during the initial information encounter, 35 whether family members were present and whether an attending physician or family member signed the witness testimony.
Informed consent - recall and understanding post-consent Do you recall agreeing to participate in this study?
…”
Section: Observational Substudiesmentioning
confidence: 99%
See 1 more Smart Citation
“…So, researcher also looked for other measures. Sometimes, the specific informed consent was not obtained 53 . Some regulations also suggested waiver of consent in emergency cases as an exception.…”
Section: Ethics Of Consent In Critically Ill or Intensive Care Unit (mentioning
confidence: 99%